2008
DOI: 10.1111/j.1742-4658.2008.06528.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant–pathogen interactions: what is proteomics telling us?

Abstract: Over the years, several studies have been performed to analyse plant–pathogen interactions. Recently, functional genomic strategies, including proteomics and transcriptomics, have contributed to the effort of defining gene and protein function and expression profiles. Using these ‘omic’ approaches, pathogenicity‐ and defence‐related genes and proteins expressed during phytopathogen infections have been identified and enormous datasets have been accumulated. However, the understanding of molecular plant–pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 80 publications
1
76
0
5
Order By: Relevance
“…This fact fits well with the purpose of this chapter and is perfectly summarized by the title of a recent paper: "Plant-pathogen interactions: what is proteomics telling us" (Mehta et al, 2008). In this paper, is shown that when pathogens are in the presence of plants, their metabolism is changed to secrete proteins, including CWDE, potentially involved in plant cell wall degradation.…”
Section: Proteomicssupporting
confidence: 52%
“…This fact fits well with the purpose of this chapter and is perfectly summarized by the title of a recent paper: "Plant-pathogen interactions: what is proteomics telling us" (Mehta et al, 2008). In this paper, is shown that when pathogens are in the presence of plants, their metabolism is changed to secrete proteins, including CWDE, potentially involved in plant cell wall degradation.…”
Section: Proteomicssupporting
confidence: 52%
“…To our knowledge, this is the first analysis of an in planta pathogen proteome ("infectome"; Mehta et al, 2008). Approximately 5% of the P. syringae DC3000 genes encode for proteins involved in virulence (Rahme et al, 1995;Preston, 2000;Buell et al, 2003).…”
Section: Application Of Cpll To Protein Extracts From Infected Leavesmentioning
confidence: 99%
“…However, systematic knowledge about in vivo plant protein phosphorylation in response to pathogen stimuli is lacking. Recently, functional genomic studies (including proteomics) have greatly contributed to the molecular dissection of plant pathogen interactions, allowing to identify a number of defense-related candidate proteins and helping to clarify specific gene expression patterns [9]. In this respect, the study of sub-proteomes has been greatly recommended to improve technical sensitivity/resolution and reduce the overall system complexity.…”
Section: Introductionmentioning
confidence: 99%